PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA ORGANISASI DI ERA TRANSFORMASI DIGITAL - Hanafi, Fahima; Irma. S. (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Digital transformation has brought significant changes to various organizational aspects, including human resource management. The role of Human Resource Management (HRM) has become increasingly strategic in addressing the challenges and opportunities arising from digital technological developments. This study aims to analyze the role of HRM in improving organizational performance in the era of digital transformation. The research method employed is a qualitative approach using a literature review by examining various relevant scholarly sources related to HRM, digital transformation, and organizational performance. The findings indicate that the implementation of digital-based HRM practices, such as digital recruitment, e-learning, performance management systems, and the development of employees’ digital competencies, positively contributes to improving organizational effectiveness and efficiency. Furthermore, the role of HRM in fostering an adaptive, innovative, and collaborative organizational culture is a key factor in supporting the success of digital transformation. Therefore, it can be concluded that HRM plays an essential and strategic role in enhancing organizational performance through adaptive human resource management in response to digital technological advancements.